PENGARUH KERJASAMA TIM, KOMPENSASI, KOMITMEN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Sastrawati, Prima; Kartika, Erawati; Sukristanta, Sukristanta (Jurnal Manajemen dan Profesional, 2025)
This study aims to determine the effect of teamwork (X1), compensation (X2), commitment (X3), and work environment (X4) on employee performance (Y).The data collection method was carried out by questionnaires to employees with a sampling technique using the slovin formula with a sample of 100 people. For the influence of teamwork, compensation, commitment, and the work environment on employee performance used statistical analysis with multiple regression methods. Data processing was carried out using the SPSS 22.0 computer program.  The results of the research show that the four independent variables are significant and have an effect on employee performance. these variables are teamwork, compensation, commitment, and work environment. The variable that has the most dominant influence on employee performance is the teamwork variable with a coefficient value of 0.615.